EDUKASI OTOMATISASI DAN ROBOTIKA DENGAN DEMONSTRASI DALAM KEGIATAN PENGABDIAN MASYARAKAT DI MTSN 1 GARUT - Wiharso, Tri arif; Iksan, Akhmad Fauzi; Nurpadillah, Sifa; Nugroho, Ginaldi Ari; Sugandi, Gandi; Agnia, Raza; Khoirul, Ahmad; Fauzan, Sadam; Heryanto, Beni (Jurnal Abdi Insani, 2025)
The development of technology in the era of the Industrial Revolution 4.0 requires an increase in technological literacy from an early age, including at the junior high school level (SMP). One way to introduce the concept of technology is through automation and robotics education. Based on this, the lecturer and student team from the Electrical Engineering Study Program at the Faculty of Engineering, Garut University, conducted community service activities in the form of education and robotics awareness to 8 MTsN 1 Garut students on May 24, 2025, with a total of 69 participants. The purpose of this activity is to foster interest, insight, and basic understanding of students about the automation system and robotics technology. The method of implementing the activity consists of the delivery of automation and robotics materials, question and answer sessions, and demonstrations of tools in the form of Line Follower robot, robot soccer, and heavy monitoring and sheep height. The results showed high levels of student participation and enthusiasm. Students look active in asking questions and trying to run robots directly. The evaluation was carried out with a satisfaction questionnaire, which showed positive results: satisfaction with the relevance of the topic of 77.33%, how to deliver 80%resource persons, the implementation of activities 78.67%, and the benefits of activities 85.33%. It can be concluded that this educational activity can increase student awareness and interest in automation and robotics technology, and can be applied to become an effective and fun Stem learning model at the junior high school level.